How does a science teacher distinguish himself as a good professional? An inquiry into the aesthetics of taste for teaching. Issue 5 (24th March 2022) - Lima Junior, Paulo; Anderhag, Per; Wickman, Per-Olof
ABSTRACT: This paper introduces the notion of taste for teaching a subject, especially science, as a conceptual framework to analyse the aesthetics of teacher development as a lifelong process. We draw on the work of Pierre Bourdieu and John Dewey in order to account for how teachers distinguish admirable practices and, in doing so, distinguish themselves as inspiring professionals. In order to illustrate this framework, we report a narrative inquiry on the life story of Tomas, a white man nationally prized for his science teaching. This inquiry was inspired by sociological portraits recommended by Bernard Lahire. Results indicate how a practical disposition (as opposed to a theoretical one) played an important role in developing Tomas's individual taste for science teaching, producing a strong continuity between his early experiences as a masculine boy raised in a family of construction workers, on the one hand, and his later experiences as a biologist and a science teacher enacting inquiry-based activities. The significance of the findings for science education is discussed.